2017
DOI: 10.1002/bab.1575
|View full text |Cite
|
Sign up to set email alerts
|

Role of palmitoylation of cysteine 415 in functional coupling CB1 receptor to Gαi2 protein

Abstract: In this study, we investigated the role of CB palmitoylation in modulating the functional interaction with G proteins both in the absence and presence of agonist binding. Our data show that the nonpalmitoylated CB receptor significantly reduced its association with Gα . The agonist stimulation induced a partial dissociation of Gα proteins from the wild-type receptor, while on the C415A mutant the agonist binding was not able to induce a significant dissociation of Gα from the receptor. The lack of palmitoyl ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The predicted topology of rat CB1R based on hydrophobicity plots and analysis from crystal structures of human CB1R (97% identity with rat CB1R) and rhodopsin-family GPCRs. Sites of post-translational modification via N-terminal glycosylation (Song and Howlett, 1995) or palmitoylation (Oddi et al, 2018(Oddi et al, , 2017(Oddi et al, , 2012 are indicated by the (Y) symbol and a red zigzag line, respectively. Two residues located within the 2nd and 3rd transmembrane domains (TM2/TM3), required for constitutive (Jin et al, 1999) internalization are shown in pink (Roche et al, 1999;D'Antona et al, 2006).…”
Section: Targeting To Late Endosomes/lysosomes From the Tgnmentioning
confidence: 99%
See 1 more Smart Citation
“…The predicted topology of rat CB1R based on hydrophobicity plots and analysis from crystal structures of human CB1R (97% identity with rat CB1R) and rhodopsin-family GPCRs. Sites of post-translational modification via N-terminal glycosylation (Song and Howlett, 1995) or palmitoylation (Oddi et al, 2018(Oddi et al, , 2017(Oddi et al, , 2012 are indicated by the (Y) symbol and a red zigzag line, respectively. Two residues located within the 2nd and 3rd transmembrane domains (TM2/TM3), required for constitutive (Jin et al, 1999) internalization are shown in pink (Roche et al, 1999;D'Antona et al, 2006).…”
Section: Targeting To Late Endosomes/lysosomes From the Tgnmentioning
confidence: 99%
“…When this residue is de-palmitoylated, membrane association of H8 ceases to be energetically favorable, so the helix unravels, causing some interaction sites to be lost and exposing other interaction sites to the aqueous domain (Sensoy and Weinstein, 2015). Overall, characterization of the non-palmitoylatable CB1R mutant suggests that palmitoylation at this site affects CB1R trafficking, localization, and signaling (Oddi et al, 2012(Oddi et al, , 2017(Oddi et al, , 2018. Specifically, blocking palmitoylation reduced plasma membrane expression, increased diffusional mobility, and prevented agonist-induced internalization of the receptor in SH-SY5Y and HEK293 cells, effects attributed to decreased association of CB1R with lipid rafts and caveolin-1 (Oddi et al, 2012(Oddi et al, , 2017.…”
Section: Palmitoylation Of Ctcb1rmentioning
confidence: 99%
“…It is noteworthy that recruitment of the CB1R to the plasma membrane as well as receptor localization at lipid rafts was impaired in nonpalmitoylated mutants, indicating the role of palmitoylation in receptor trafficking and localization. In addition, nonpalmitoylated CB1R significantly reduced receptor association with G α i-subunit, demonstrating that palmitoylation may be responsible for the functional transmission of the agonist-induced conformational changes from receptors to the G protein [ 7 ]. Similar to that of the MOR, palmitoylation of the CB1R seems to be involved in the modulation of the conformational state of helix 8 and interactions of the CB1R with cholesterol and caveolin 1 [ 6 ].…”
Section: Palmitoylation Of G Protein-coupled Receptors (Gpcrs)mentioning
confidence: 99%
“…More recently, proteomic approaches applied to study global palmitoylation of neuronal proteins have confirmed palmitoylation of endogenously expressed neurotransmitter receptor under in vivo conditions [ 4 , 5 ]. Disruption of palmitoylation could significantly affect a variety of neurotransmitter receptors properties, including conformation [ 6 , 7 ], trafficking and localization on the plasma membrane [ 8 , 9 ], and downstream signaling [ 10 , 11 ]. This review summarizes our current knowledge on the palmitoylation of neurotransmitter receptors and its role in the regulation of receptors functions and, as consequence, in the control of different kinds of physiological and pathological behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, as a preeminent member of G‐protein‐coupled receptors (indeed, the most abundant member of the GPCR family in our brain), CB 1 can be functionally modulated by membrane lipids. The experimental work by Oddi and colleagues demonstrates the role of palmitoylation of CB 1 in controlling its location and functional interaction with the plasma membrane, and its association with Gαi2 protein . Oddi and colleagues propose that the control of the reversible reaction of palmitoylation offers a new opportunity for CB 1 regulation and could open novel therapeutic approaches.…”
mentioning
confidence: 99%